Virtual three-dimensional model for preoperative planning in a complex case of a double outlet right ventricle - Swati Garekar; Alpa Bharati; Firoza Kothari; Sachin Patil; Shyam Dhake; Shivaji Mali; Amit Mhatre; Dilip Bind; Ashwini Joshi; Bharat Soni; Dhananjay Malankar (Wolters Kluwer Medknow Publications, 2019)
A 3-year-old child with a complex variant of double outlet right ventricle achieved a successful biventricular repair after detailed delineation of the intracardiac anatomy on multimodality imaging. A virtual three-dimensional (3D) model based on computed tomography was used successfully in the absence of an actual 3D-printed model. This case report seeks to highlight and hence increase the utilization of the virtual 3D model in resource-limited settings.